2016
DOI: 10.1108/ilt-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviours of surface-modified serpentine powder as lubricant additive

Abstract: Purpose – The aim of this paper is to study the tribological performance and self-repairing performance of surface-modified nanoscale serpentine powders as lubricant additives in the mineral base oil (5-CST). Design/methodology/approach – Fourier transform infrared spectroscopy spectra and thermo-gravimetric analysis of both modified and unmodified serpentine were performed to analyse their grafting ratio and suspension after modified us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Magnesium silicate hydroxide (MSH), as the main component of serpentine, has been studied widely for its environmentally friendly capacity, low price, and excellent tribological performance . Yu et al and Zhang et al demonstrated that ultrafine serpentine could conduce to the formation of a super‐hard oxide layer which possesses good wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium silicate hydroxide (MSH), as the main component of serpentine, has been studied widely for its environmentally friendly capacity, low price, and excellent tribological performance . Yu et al and Zhang et al demonstrated that ultrafine serpentine could conduce to the formation of a super‐hard oxide layer which possesses good wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of OA‐MSH is 1.0 wt%, the friction surface is the smoothest and contains more micropores, which is a typical self‐repairing layer morphology. Figure 7D, when the content of OA‐MSH is 1.5 wt%, many burrs will appear, indicating that excessive OA‐MSH will cause abrasive wear and increase the WR 32 …”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of friction pair surface layer is commonly studied using energy dispersive X-ray spectroscopy (EDS) coupled with scanning electron microscopy, X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES), while the phase composition and structure characteristics are usually observed through transmission electron microscopy (TEM) and atomic-force microscopy (AFM). Numerous studies have reported that the Si and Mg contents of most friction pairs treated with AMNP (Figure 10, middle image) were significantly higher than that of without AMNP [14,[21][22][23]26,27,[49][50][51][52][53]55,56,61,69,72,77,85,91,[94][95][96][97][98][99]. Some friction pair surfaces treated with AMNP only detected Si but no Mg [17,25,54,55,64,66,74,78,79,84,86,91,95], or only detected Mg but no Si [18,60,100], or neither Si nor Mg were detected [5...…”
Section: Physico-chemical Characteristics Of a Friction Pair Surfacementioning
confidence: 99%